2021
DOI: 10.3390/brainsci11050591
|View full text |Cite
|
Sign up to set email alerts
|

Differential Alterations in Resting State Functional Connectivity Associated with Depressive Symptoms and Early Life Adversity

Abstract: Depression and early life adversity (ELA) are associated with aberrant resting state functional connectivity (FC) of the default mode (DMN), salience (SN), and central executive networks (CEN). However, the specific and differential associations of depression and ELA with FC of these networks remain unclear. Applying a dimensional approach, here we analyzed associations of FC between major nodes of the DMN, SN, and CEN with severity of depressive symptoms and ELA defined as childhood abuse and neglect in a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
(116 reference statements)
3
15
1
Order By: Relevance
“…However, recent clinical studies indicate that the role of the RPFC node of the Salience Network in emotion processing may be more complex than previously thought. For example, alterations in network functional connectivity associated with depressive symptoms were directly linked to dysfunctions in the RPFC (Fadel et al, 2021). It is worth mentioning that the left RPFC node in our study overlaps with previously reported ''the dorsal nexus''-a so-called area in the prefrontal cortex that showed aberrant functional connectivity with the DMN, attention network and cognitive control network by hot-wiring them together in depression (Sheline et al, 2010).…”
Section: Positive Emotionsupporting
confidence: 82%
“…However, recent clinical studies indicate that the role of the RPFC node of the Salience Network in emotion processing may be more complex than previously thought. For example, alterations in network functional connectivity associated with depressive symptoms were directly linked to dysfunctions in the RPFC (Fadel et al, 2021). It is worth mentioning that the left RPFC node in our study overlaps with previously reported ''the dorsal nexus''-a so-called area in the prefrontal cortex that showed aberrant functional connectivity with the DMN, attention network and cognitive control network by hot-wiring them together in depression (Sheline et al, 2010).…”
Section: Positive Emotionsupporting
confidence: 82%
“…For example, it was proposed that the RPFC is coupled with the DMN and posterior parietal cortices during emotion processing in healthy individuals. However, in aberrant functional connectivity within nodes of the DMN, FPN and SN, the RPFC ‘hot‐wires’ the tree networks together, leading to various depressive symptoms (Fadel et al, 2021; Scalabrini et al, 2020; Sheline et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a large adolescent sample, Rakesh et al (2021a) found differential effects of threat and deprivation across development: at age 16, greater abuse was associated with less within salience network connectivity, while at age 19, greater neglect was associated with greater within-salience network connectivity, potentially indicating different trajectories for adversity dimensions. Fadel et al (2021) also found differential relationships of threat and deprivation on salience network connectivity; in a sample of healthy and depressed adults they found opposing relationships of abuse and neglect on within salience network connectivity (i.e., prefrontal cortex-insula), in which greater abuse was associated with greater resting-state connectivity and greater neglect was associated with less restingstate connectivity. The present study did not find effects of socioeconomic deprivation, as defined by maximum parental education level (reverse coded), on any ROI-to-ROI connection.…”
Section: Differential Relationships Of Childhood Threat and Deprivati...mentioning
confidence: 88%
“…Several studies have examined differential relationships between resting-state connectivity and aspects of threat and deprivation dimensions ( Cheng et al, 2021 ; Fadel et al, 2021 ; Park et al, 2021 ; Rakesh et al, 2021a ). A study examining mesocorticolimbic circuitry in young children found opposing influences of threat and socioeconomic deprivation on ventral tegmental area (VTA)-related resting-state connectivity ( Park et al, 2021 ), with greater threat associated with less VTA-somatomotor connectivity and greater deprivation associated with greater VTA-intraparietal sulcus connectivity.…”
Section: Discussionmentioning
confidence: 99%